2022
DOI: 10.1088/1538-3873/ac6c09
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Obliquities in Exoplanetary Systems

Abstract: The rotation of a star and the revolutions of its planets are not necessarily aligned. This article reviews the measurement techniques, key findings, and theoretical interpretations related to the obliquities (spin–orbit angles) of planet-hosting stars. The best measurements are for stars with short-period giant planets, which have been found on prograde, polar, and retrograde orbits. It seems likely that dynamical processes such as planet–planet scattering and secular perturbations are responsible for tilting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 513 publications
2
67
0
Order By: Relevance
“…We find that ZLK migration generates primarily retrograde stellar obliquities, with a broad peak around 90°(see Figure 4) on a timescale of 10 7 -10 9 yr. Over time, many of these host stars may evolve toward a perpendicular orientation due to stellar tides. Our result may therefore provide a possible explanation for the recently claimed "preponderance of perpendicular planets" among HJ systems (Albrecht et al 2021(Albrecht et al , 2022.…”
Section: Discussionsupporting
confidence: 59%
“…We find that ZLK migration generates primarily retrograde stellar obliquities, with a broad peak around 90°(see Figure 4) on a timescale of 10 7 -10 9 yr. Over time, many of these host stars may evolve toward a perpendicular orientation due to stellar tides. Our result may therefore provide a possible explanation for the recently claimed "preponderance of perpendicular planets" among HJ systems (Albrecht et al 2021(Albrecht et al , 2022.…”
Section: Discussionsupporting
confidence: 59%
“…This suggested that the star's rotation axis has a low inclination and -if the orbit is aligned with the star-the orbit is viewed nearly face on. The premise of good alignment was reasonable at the time but was eventually undermined by the discovery of severe misalignments between stars and the orbits of shortperiod giant planets (see Albrecht et al 2022 for a review).…”
Section: Hd 111232mentioning
confidence: 99%
“…Although an (exo)planet`s insolation regime depends on various parameters, including orbital eccentricity and the obliquity of its spin axis (Dobrovolski 2013), they may be also candidate parameters, which affect its atmosphere and the climate. The former, eccentricity, increases the annual averaged ux, received by the planet (e.g., the possibility of global freezing in the case of an eccentric exoplanet) ( Measuring a star's obliquity is challenging because ordinary observations lack the angular resolution to discern any details on the spatial scale of the stellar surface (Albrecht et al 2022). For such reasons, obliquity is not considered one of the key parameters in this phase of the research.…”
Section: Components 2 -Formation Criteria and Persistency Ofmentioning
confidence: 99%